Electric Actuation of Nanostructured Thermoplastic Elastomer Gels with Ultralarge Electrostriction Coefficients - Kim, Bori; Park, Youn Duk; Min, Kyoungho; Lee, Jin Hong; Hwang, Seung Sang; Hong, Soon Man; Kim, Bong Hoon; Kim, Sang Ouk; Koo, Chong Min (WILEY-BLACKWELL, 2011)
Electrostriction facilitates the electric field-stimulated mechanical actuation of dielectric materials. This work demonstrates that introduction of dielectric mismatched nanodomains to a dielectric elastomer results in an unexpected ultralarge electrostriction coefficient, enabling a large electromechanical strain response at a low electric field. This strong electrostrictive effect is attributed to the development of an inhomogeneous electric field across the film thickness due to the high density of interfaces between dielectric mismatched periodic nanoscale domains. The periodic nanostructure of the nanostructured gel also makes it possible to measure the true electromechanical strain from the dimensional change monitored via in situ synchrotron small angle X-ray scattering. The work offers a promising pathway to design novel high performance dielectric elastomers as well as to understand the underlying operational mechanism of nanostructured multiphase electrostrictive systems.
Keywords: HIGH-DIELECTRIC-CONSTANT; ANGLE NEUTRON-SCATTERING; FIELD-INDUCED STRAIN; ELECTROMECHANICAL RESPONSE; POLYURETHANE ELASTOMER; COPOLYMER; COMPOSITES; POLYMERS; BEHAVIOR; FILMS